2019
DOI: 10.1177/0957650918824013
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of slotted diffuser effects on a highly loaded centrifugal compressor

Abstract: Flow separations in the vaned diffuser play a critical role in the stall margin of centrifugal compressors. To extend the stable operating range of a highly loaded centrifugal compressor, a flow control technique of locating a slot near the vaned diffuser's leading edge is proposed. A parametric study of slot geometry variations, in terms of the slotted portion depth and length, is carried out to summarize the trend of compressor performance and to reveal the corresponding flow physics related to the slot geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The design of compact and efficient diffuser is very challenging, and it is also a major technical obstacle for the high-pressure-ratio centrifugal compressors [6,7]. At present, there are many researches on the design of the diffusers, such as low solidity vanes, half guide vanes, pipe diffuser and leading edge slotted design, these could improve the performance of the diffusers [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The design of compact and efficient diffuser is very challenging, and it is also a major technical obstacle for the high-pressure-ratio centrifugal compressors [6,7]. At present, there are many researches on the design of the diffusers, such as low solidity vanes, half guide vanes, pipe diffuser and leading edge slotted design, these could improve the performance of the diffusers [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The size of the roughness elements is increased at the same design condition from smooth surface to roughness magnitudes of (50 μm, 100 μm, 200 μm) and compared with the baseline compressor, which indicates that stall margin has been increased in each case of roughness heights by simulating it using SST turbulence model. However, there is drastic drop in total pressure ratio and isentropic efficiency with the increase in the roughness heights as compared to the slotted diffuser studied by Yingjie et al [ 13 ]. The most significant drop in pressure ratio was observed when roughness magnitude rose to 200 μm.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that when the air flow angle of incidence increases at the inlet of diffuser, the aerodynamics load decreases and the flow structure of the diffuser vaneless region improves significantly. Yingji et al [ 13 ] studied the parametric analysis of slotted diffuser geometry variation to augment the stable operating range of the high-pressure ratio centrifugal compressor. Their analysis concluded that at reduced mass flow rate, there is flow separation at the corner of diffuser hub, which has been eliminated by the length of slot, which was 8–16% of chord length of diffuser without significant deterioration in performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much investigation has focused on the structure of the diffuser blade itself, including its low solidity, partial blade height, and slotted leading edge. 710 Ubben et al. 11 studied the effects of a diffuser on compressor performance using a variable speed control and adjustable diffuser clearance height.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much investigation has focused on the structure of the diffuser blade itself, including its low solidity, partial blade height, and slotted leading edge. [7][8][9][10] Ubben et al 11 studied the effects of a diffuser on compressor performance using a variable speed control and adjustable diffuser clearance height. Onesided diffuser clearance showed no negative impact on the operation or loss behavior of the centrifugal compressor, while improving its pressure ratio and efficiency.…”
Section: Introductionmentioning
confidence: 99%